2001
DOI: 10.1021/jo001079t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design and Synthesis of Artificial Ion Channels Based on Cyclic Peptides Containing Unnatural Amino Acids

Abstract: A series of novel cyclic peptides composed of 3 to 5 dipeptide units with alternating natural-unnatural amino acid units, have been designed and synthesized, employing 5-(N-alkanoylamino)-3-aminobenzoic acid with a long alkanoyl chain as the unnatural amino acid. All cyclic peptides with systematically varying pore size, shape, and lipophilicity are found to form ion channels with a conductance of ca. 9 pS in aqueous KCl (500 mM) upon examination by the voltage clamp method. These peptide channels are cation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 73 publications
0
42
0
2
Order By: Relevance
“…[33][34][35] UV-vis titration experiments in DMSO indicated that the disodium salt of 4-nitrophenyl phosphate forms 1 : 1 complexes with the receptors [K a = 1.2 Â 10 6 M À1 for cyclo-(Ala-Aba) 3 (4)]. Additional evidence for the binding mode was obtained by 1 H NMR spectroscopy, which indicates that 4 has C 3 -symmetry that is maintained on binding the phosphoester.…”
Section: Simple Cyclic Peptidesmentioning
confidence: 97%
“…[33][34][35] UV-vis titration experiments in DMSO indicated that the disodium salt of 4-nitrophenyl phosphate forms 1 : 1 complexes with the receptors [K a = 1.2 Â 10 6 M À1 for cyclo-(Ala-Aba) 3 (4)]. Additional evidence for the binding mode was obtained by 1 H NMR spectroscopy, which indicates that 4 has C 3 -symmetry that is maintained on binding the phosphoester.…”
Section: Simple Cyclic Peptidesmentioning
confidence: 97%
“…[60] Intramolecular native chemical ligation has also been used to create cyclic peptides and proteins. [61][62][63] Chemical synthesis allows a large variety of unnatural amino acids to be incorporated into peptides and proteins. It is particularly useful for the incorporation of amino acid analogues that are toxic to cells or incompatible with the translational machinery (for example, the synthesis of an all d-amino acid protein [64,65] ).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…For an organic chemist entering the field without BLMs, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] LUVs provide a user friendly and, according to the comparative studies discussed below, valid alternative. Among several possible methods to determine anion/cation selectivity of synthetic ion channels in vesicles, the HPTS assay worked best in our hands (Fig.…”
Section: Determination Of Anion/cation Selectivity In Vesicles For Symentioning
confidence: 99%